2005
DOI: 10.1007/s11165-004-8163-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Difficulties of Teachers Who Mentor Environmental Inquiry Projects

Abstract: The paper describes characteristics and analyses difficulties of environmental sciences teachers in mentoring their students in an extended inquiry project, which is a mandatory requirement of the environmental sciences matriculation in Israel. The teachers participated in a professional development program that provided both content knowledge and support for conducting inquiry, and enabled the teachers to guide the students in the inquiry project. Teachers who had experience in inquiry identified more skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Personal courage is by far perceived as the single most significant factor within this category. It is perceived to take courage to be able to let go of control, which is in coherence with previous studies where teachers express fears of what might happen when including CSS (Aikenhead, 2004;Bencze & Hodson, 1999;Braund & Reiss, 2006;Crawford, 1999;Fishman et al, 2003;Tal & Argaman, 2005). Dare to let go of the control.…”
Section: (3) 2012supporting
confidence: 84%
See 1 more Smart Citation
“…Personal courage is by far perceived as the single most significant factor within this category. It is perceived to take courage to be able to let go of control, which is in coherence with previous studies where teachers express fears of what might happen when including CSS (Aikenhead, 2004;Bencze & Hodson, 1999;Braund & Reiss, 2006;Crawford, 1999;Fishman et al, 2003;Tal & Argaman, 2005). Dare to let go of the control.…”
Section: (3) 2012supporting
confidence: 84%
“…Bungum (2003) adds struggles with the timetable to the list of teachers' perceived barriers. Teachers' concern regarding lack of control over the entire content knowledge is clearly expressed in studies on projects involving interdisciplinary (Tal & Argaman, 2005) as well as inquiry-based learning (Crawford, 1999;Fishman, Marx, Best & Tal, 2003).…”
Section: The Teacher's Role In Relation To Cssmentioning
confidence: 99%
“…In 33 articles (for example, [1,4,5,11,12,19,29,[43][44][45]), the authors provided a definition of PBSTL, 6 either in a clearly identified section (25 articles) or indirectly throughout the text (8 articles). In 15 texts, the authors did not provide a definition for this approach (for example, [6][7][8][9]14,15,18,39]).…”
Section: The Concepts and Features Used To Define Them (Q1)mentioning
confidence: 99%
“…It is a question of the students being involved in the S&T processes used to solve the problem or answer the central question: scientific inquiry ( [19,26,38,43]); investigation ( [1,4,19,25,29,31,32,43,44]); and engineering design ( [25,29] The authors typically prefer the latter type of inquiry for PBSTL.…”
Section: The Students Are Engaged In Investigations or Design Activitiesmentioning
confidence: 99%
See 1 more Smart Citation